Chasing targets in a pandemic: The impact of COVID-19 on HIV outreach workers for MSM (men who have sex with men) in Jakarta, Indonesia. Issue 11 (2nd November 2021) - Hegarty, Benjamin; Handayani, Amalia; Nanwani, Sandeep; Praptoraharjo, Ignatius
ABSTRACT: The COVID-19 pandemic has had a significant impact on HIV services globally, including community-based outreach programmes. This article draws on a qualitative study of HIV outreach workers for men who have sex with men (MSM) in Jakarta, Indonesia undertaken between July and September 2020. The research documented the impact of the COVID-19 pandemic on HIV outreach programmes for MSM based on interviews, focus group discussions and video diaries collected from outreach workers. As a result of the pandemic, and in response to the guidelines issued by international donors and the Indonesian government, outreach workers shifted activities to 'virtual outreach' where possible. However, outreach workers consistently performed in-person work to address what they referred to as 'urgent' cases (e.g. required them to attend the clinic). Regardless of delivery mode, the steps comprising outreach work during the pandemic aligned with the 'cascade of care', which forms the dominant policy narrative for the management of HIV. Outreach work during the pandemic therefore continued to be based primarily on the objective of maintaining testing and treatment rates. Although outreach workers responded innovatively to the pandemic, including to the risk of COVID-19 infection, they were limited by the prevailing emphasis on targets in HIV programmes.